Pharmaceutical Study of Gauri Gairikadhya Churna (AYUSHDHARA, 2025)
Ayurveda is one of the most ancient health care systems. The main aim of Ayurveda is Swasthasya swasthya rakshanam Aturasya vikara prashamanam i.e.; promotion of health and eradication of diseases. The disease Vyanga is one of the Kshudra roga. Many formulations have been described in our classical texts regarding Vyanga. One among them is Gauri gairikadhya Churna. Gauri gairikadhya churna is a classical herbo-mineral formulation mentioned in Basavarajeeyam, Kshudra roga adhikara indicated for Vyanga as a Lepa. Lepa preparations are topical medicaments meant for external application. Gauri gairikadhya churna contains Haridra, Daruharidra, Manjishta, Goghrita, Gaura sarshapa, Gairika, Ajaksheera (as Bhavana Dravya). The pharmaceutical procedure adopted in this study are Shodhana, Churna nirmana and Bhavana of Gauri gairikadhya churna. Bhavana of the Churna is done with Aja ksheera which adds more potency to the formulation. Till now, no research work has been carried out to standardize the method of preparation of Gauri gairikadhya churna. Therefore, the present study has been carried out to standardize the method of preparation of Gauri gairikadhya churna mentioned in classics.